Education norms and models circulation in west Africa: the role of social actors - (:unkn) unknown (My University, 2013)
Panel Inequalities and multi-governance levels in education public policies in Africa, mod. Muriel Gomez-Perez, Hélène Charton, Marie-Christine Deleigne, Hamidou Dia http://www.nomadit.co.uk/ecas/ecas2013/panels.php5?PanelID=2367
Keywords: African Research